Revitalization of Rajasyah Outbound & Edu Center As Edutourism Based Tourism Object (International Journal of Architecture and Urbanism, 2021)
Abstract.Rajasyah Outbound & Edu Center are tourist attractions in North Sumatra, precisely on Bunga Pariama street, Namu Gajah, Kec. Medan Tuntungan. This tourism has decreased vitality so that few visitors come to the place, will do to revive something that was previously empowered, namely using revitalization by identifying the causes of the decline in the vitality of the area and assessing the potential in the area to increase tourism vitality again. This research is base on predetermined variables, named the theory of elements of the city images. This study uses descriptive qualitative methods obtains through observations, interviews, and literature studies. At the end of the discussion, this study will provide recommendations for a tourism revitalization design model with the theories used. By discussing the analysis and recommendations of the design model, is expected to be a guide in developing tourist areas in Medan so that it can increase good economic income for the region.